Intra‐host diversity and evolution of hepatitis C virus endemic to Côte d'Ivoire. Issue 5 (12th February 2014) - Forbi, Joseph C.; Campo, David S.; Purdy, Michael A.; Dimitrova, Zoya E.; Skums, Pavel; Xia, Guo‐liang; Punkova, Lili T.; Ganova‐Raeva, Lilia M.; Vaughan, Gilberto; Ben‐Ayed, Yousr; Switzer, William M.; Khudyakov, Yury E.
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) infection presents an important, but underappreciated public health problem in Africa. In Côte d'Ivoire, very little is known about the molecular dynamics of HCV infection. Plasma samples (n = 608) from pregnant women collected in 1995 from Côte d'Ivoire were analyzed in this study. Only 18 specimens (∼3%) were found to be HCV PCR‐positive. Phylogenetic analysis of the HCV NS5b sequences showed that the HCV variants belong to genotype 1 (HCV1) (n = 12, 67%) and genotype 2 (HCV2) (n = 6, 33%), with a maximum genetic diversity among HCV variants in each genotype being 20.7% and 24.0%, respectively. Although all HCV2 variants were genetically distant from each other, six HCV1 variants formed two tight sub‐clusters belonging to HCV1a and HCV1b. Analysis of molecular variance (AMOVA) showed that the genetic structure of HCV isolates from West Africa with Côte d'Ivoire included were significantly different from Central African strains (P = 0.0001). Examination of intra‐host viral populations using next‐generation sequencing of the HCV HVR1 showed a significant variation in intra‐host genetic diversity among infected individuals, with some strains composed of sub‐populations as distant from each other as viral populations from different hosts. Collectively, the results indicate a complex HCV evolution in Côte d'Ivoire, similar to the rest of West Africa, and suggest a unique HCV epidemic history in the country. J. Med. Virol. 86:765‒771, 2014. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.